The Use of Poly(Vinyl Alcohol) to Cross‐link Penicillinase for the Fabrication of a Penicillin Potentiometric Biosensor. Issue 12 (12th November 2014) - Ismail, Fatima; Adeloju, Samuel B.
Abstract Chemically cross‐linked PVA films are permeable matrices for the fabrication of biosensors. PVA provides an attractive immobilisation method as it preserves the enzymatic activity. Penicillinase (P'nase) was cross‐linked with poly(vinyl alcohol) (PVA) and bovine serum albumin (BSA). The optimum conditions for the of BSA‐PVA‐P'nase film were: 2.5 % w/v PVA, 0.006 % w/v BSA, 2.4 mM penicillin (Pen) and 16 U/mL P'nase. The minimum detectable concentration was 1.7 µM. The linear concentration range obtained for the BSA‐PVA film was 7.5–283 µM. The BSA‐PVA P'nase biosensor detected penicillin in amoxycillin with an average percentage recovery of 97±12 %. Higher penicillin concentrations (10–20 ppm) were detected more successfully than lower concentrations (≤5 ppm). These results indicate that further work is required to enable the successful detection of lower penicillin concentrations such as 5 ppm.